Mediating positive moods: the impact of experiencing compassion at work. (16th December 2014) - Chu, Li‐Chuan
Abstract : Aim: The aim of this study was to examine the mediating effects of positive moods underlying the relationship between experiencing compassion at work and both job performance and organisational citizenship behaviour (OCB). Background: Employees who have experienced compassion might have more positive moods while at work; such moods have been connected to a host of important organisational outcomes such as better job performance and OCB. Methods: This study adopted a two‐stage survey whose participants consisted of 269 registered nurses employed by hospitals in Taiwan. All hypotheses were tested using hierarchical regression analyses. Results: The results showed that positive moods mediate completely the relationship between experiencing compassion at work and both job performance and OCB. Conclusion: When nurses frequently feel that their hospital, supervisors or co‐workers are willing to listen to them, the strength that arises from this compassion can effectively increase job performance and OCB though the positive moods process. Implications for nursing management: It is importance to cultivate a compassionate and caring culture throughout hospitals' hierarchies, especially from the top down. Nurses will have more opportunities to experience it, witness it, or participate in it when they work within a compassionate and caring organisational culture.